COMMUNAL LAND CONFLICT IN THE PERSPECTIVE OF DEVELOPMENT STUDIES: IMPLICATIONS FOR THE ECONOMY OF MEDAN CITY - Mukhrizal Effendi (RADJA PUBLIKA, 2026)
This study examines communal land (tanah ulayat) conflicts in Medan City from a development studies perspective and analyzes their implications for local economic performance. Rapid urban expansion, infrastructure development, and increasing land demand have intensified tensions between customary land tenure systems and formal land administration. The study aims to identify the structural causes of communal land conflicts, assess their economic impacts, and propose governance-oriented solutions to support sustainable urban development. A qualitative case study approach combined with descriptive quantitative analysis was employed, using in-depth interviews, field observations, document analysis, and secondary economic data. The findings indicate that communal land conflicts contribute to slower investment growth, project delays, increased development costs, and land price volatility. Regression analysis shows that property rights security, investment levels, and governance effectiveness significantly influence local economic performance, explaining approximately 68% of its variation. These results highlight that unresolved land conflicts are not only legal issues but also development constraints affecting economic stability. Strengthening land governance integration, legal harmonization, and participatory conflict resolution mechanisms is essential to enhance investment certainty and promote inclusive, sustainable urban economic development in Medan City.